Interferon regulatory factor 7 in inflammation, cancer and infection - Qing, Furong; Liu, Zhiping (Frontiers in Immunology, 2023)
Interferon regulatory factor 7 (IRF7), a member of the interferon regulatory factors (IRFs) family, is located downstream of the pattern recognition receptors (PRRs)-mediated signaling pathway and is essential for the production of type Ⅰ interferon (IFN-Ⅰ). Activation of IRF7 inhibits various viral and bacterial infections and suppresses the growth and metastasis of some cancers, but it may also affect the tumor microenvironment and promote the development of other cancers. Here, we summarize recent advances in the role of IRF7 as a multifunctional transcription factor in inflammation, cancer and infection by regulating IFN-Ⅰ production or IFN-Ⅰ-independent signaling pathways.